Postures professionnelles des conseillers en évolution professionnelle - Anne Jorro (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This text studies the professionalisation of the professionals of the council invited to mobilize new occupational postures within the framework of the law on the council in occupational evolution. After a reflection on the specificity of the activity of council, on the idea even of occupational evolution, the concepts of occupational posture and gestures professional are studied. The device of research – formation, co-builds with learners (12 professionals), understands 10 situations of analysis of practice. The results of this exploratory research show the importance of the postures and the professional gestures in the accompaniment of the actors. If the activity of council is understood with the professional postures and gestures which structure it, it still remains to deepen from the point of view of interactive dynamics between the advisor and the recipient of the council.